THE RELATIONSHIP BETWEEN FAMILY SUPPORT SYSTEM AND CHILD ANXIETY LEVELS BEFORE CIRCUMCISION - Bitcar, Bitcar; Idris, Syamsul; Mora, Gunawan Lelo (Jurnal Keperawatan Respati Yogyakarta, 2022)
The problem of anxiety in children before circumcision is still found, this anxiety has an impact on the psychological problems of children undergoing circumcision, so the role of the family in accompanying it is needed. One of the roles of the family that is thought to be related to children's anxiety is the family support system. The purpose of this study was to determine the relationship between the family support system and the child's level of anxiety before circumcision. This type of research used descriptive correlation with cross sectional design, the population in this study were all children who were circumcised at the Fathiyah Husada medical center. The sampling technique was accidental sampling, the number of samples was 21 people. The instrument used was a family support system questionnaire sheet and a child anxiety questionnaire. Data analysis was carried out with univariate and bivariate using Spearmen Rho test. The results showed that the Family Support System with good categories were 12 families (57.1%), the majority of children's anxiety levels were mild as many as 9 respondents (42.9%). The results of statistical tests using Spearmen Rho showed the relationship between the family support system and the child's level of anxiety before circumcision was obtained p-value = 0.000 (p<0.05). Conclusion of the study showed that there was a relationship between the family support system and the child's level of anxiety before circumcision. It is hoped that families can improve the support system for children who will undergo circumcision, so that the anxiety experienced by children can be minimized. Keywords: Family support system; Anxiety; Circumcision